La semana de cookie - Ward, Cindy; DePaola, Tomie, 1934- (New York : Scholastic, 2000)
Cookie the cat gets into a different kind of mischief every day of the week.
Reprint: Originally published: New York : Putnam, c1988.
"First Scholastic printing, September 2000"--T.p. verso.
"This edition is only available for distribution through Book Clubs and Book Fairs."--P. [4] of cover.
RL1.
004-007.
Accelerated Reader AR
Keywords: Cats -- Fiction; Days -- Fiction; Spanish language materials -- Juvenile fiction; Cats -- Juvenile fiction; Days -- Juvenile fiction